2016
DOI: 10.1111/jai.13040
|View full text |Cite
|
Sign up to set email alerts
|

Growth and life history traits of Aegean chub, Squalius fellowesii (Günther, 1868) in streams in Muğla Province, Aegean coast, Turkey

Abstract: Summary To aid in species' conservation, the aim of this study was to provide initial findings on age, growth and reproduction of an endemic species, Aegean chub Squalius fellowesii (Günther, 1868) populations from streams in the Aegean region of Muğla Province, Turkey. The species is relatively short‐lived (maximum 6 years), attaining a size of about 200 mm total length with a rapid growth to first maturity (≈60 mm TL), and relatively little growth thereafter. The male:female ratio was 1.0 : 0.6, males signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…However, given the overall pronounced niche differentiation observed in the present study, non-native L. gibbosus and P. parva at this stage may be considered not to pose a threat to the endemic species of Sarıçay Stream. Indeed, endemic S. fellowesii was found in high abundance, similar to other streams and lakes of the Aegean region (Özdemir et al, 2015;Top et al, 2016). Overall, the present results support recent findings on feeding interactions between native and non-native fishes (Karakuş, 2014;Jackson et al, 2016) and suggest that the potential for adult L. gibbosus to cause adverse impacts through habitat competition with the native species is not apparent in Sarıçay Stream.…”
Section: Discussionsupporting
confidence: 90%
“…However, given the overall pronounced niche differentiation observed in the present study, non-native L. gibbosus and P. parva at this stage may be considered not to pose a threat to the endemic species of Sarıçay Stream. Indeed, endemic S. fellowesii was found in high abundance, similar to other streams and lakes of the Aegean region (Özdemir et al, 2015;Top et al, 2016). Overall, the present results support recent findings on feeding interactions between native and non-native fishes (Karakuş, 2014;Jackson et al, 2016) and suggest that the potential for adult L. gibbosus to cause adverse impacts through habitat competition with the native species is not apparent in Sarıçay Stream.…”
Section: Discussionsupporting
confidence: 90%
“…It is likely that, once stocked into ponds where fish are absent or low in abundance, as for the study ponds, food resources are poorly exploited, thus permitting brief increases in growth rates. This situation may contrast with the fish‐filled environments characteristic of the ponds from which crucian carp were stocked where higher fish densities may have depleted available food resources (Holopainen et al, 1997), resulting in the more typically observed pattern of declining growth rates with age (Tarkan & Vilizzi, 2015; Top, Tarkan, Akbaş, & Karakuş, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is an endemic species of Western Anatolia water resources, there is still a lack of studies for local knowledge on the biological data of the S. fellowesii. In some of the limited studies, the LWRs of the species were evaluated: b = 2.760, from Işıklı Lake by Balık et al (2002); as b = 2.802, from İkizcetepeler Reservoir by Koç et al (2007); in 12 different sampling station between b = 2.9 -3.4, from Muğla Province by Top et al (2016), b = 2.607, from Küçükler Reservoir; and b = 2.597 from Buldan Reservoir by Güçlü and Küçük (2021), which is a very recent study from the Gediz River Basin. Most of the previous studies have been discussed from the reservoirs except for Işıklı Lake (Denizli province).…”
Section: Lwrs Analysismentioning
confidence: 99%
“…There are some local studies for these species, which are related to its distribution and some biological features (Şaşı, Balık 2003;Balık et al 2004;Şaşı 2004;Koç et al 2007). Virtually no information has been made available recently except for a few studies on the distribution and ecology of freshwater fish (Özdemir et al 2015) and some biological treatments as growth and life history traits, including the S. fellowesii (Gianetto et al 2012;Top et al 2016).…”
Section: Introductionmentioning
confidence: 99%